The packraft handbook : an instructional guide for the curious - Mehl, Luc (Mountaineers Books, 2021)
"The Packraft Handbook is a comprehensive guide to packrafting, with a strong emphasis on skill progression and safety. Readers will learn to maneuver through river features and open water, mitigate risk with trip planning and boat control, and react when things go wrong. Illustrated for visual learners and featuring stunning photography, The Packraft Handbook has something to offer all packrafters." -- Back cover.